Lags and Leads in Life Satisfaction: A Test of the Baseline Hypothesis - Andrew E. Clark; Ed Diener; Yannis Georgellis; Richard E. Lucas (Deutsches Institut für Wirtschaftsforschung (DIW), 2008)
We look for evidence of habituation in twenty waves of German panel data: do individuals, after life and labour market events, tend to return to some baseline level of well-being? Although the strongest life satisfaction effect is often at the time of the event, we find significant lag and lead effects. We cannot reject the hypothesis of complete adaptation to marriage, divorce, widowhood, birth of child, and layoff. However, there is little evidence of adaptation to unemployment for men. Men are somewhat more affected by labour market events (unemployment and layoffs) than are women, but in general the patterns of anticipation and adaptation are remarkably similar by sex.
Keywords: I31; J12; J13; J63; J64; 330; Life satisfaction; anticipation; adaptation; baseline satisfaction; labour market and life events